The Empirical Relationship Between Economic Growth, ICT, Financial Globalization Uncertainty and Financial Development: Evidence from Selected Leading African Economies - Zunaidah, Sulong; Ibrahim Sambo, Farouq; Saádatu Suleiman, Sanusi (2020)
The paper concentrated on six selected major African countries from 1990 to 2011 and describes the effect of ICT-driven institutional efficiency and knowledge exchange systems on economic growth, financial globalization, and economic growth on financial development. That is because the financial markets of both of those nations are underdeveloped. The article applied Larsson's co-integration, the dynamic common correlated effect, and PMG estimates. The findings indicate a positive long-term association for all parameters, which involves the interaction term. Nevertheless, it is worthy of note that financial globalization is inevitable, as its repercussions can only be ignored at the cost of growth in the country. Perhaps it guarantees that ICT-driven knowledge exchange and institutional quality frameworks contribute to the speeding up of the financial development of the six sampled leading African countries. Increasing knowledge sharing powered by ICT across countries could solve one of the major obstacles of African business activities: which is; lack of financial ease of access. Sampled nations can also optimize ICT-driven knowledge-sharing to decrease asymmetric information. The article provides a full set of recommendations for the sampled countries.